Different types of screen-based sedentary time and anxiety in adolescents: Video games may be more important - Sitong Chen; Cain C. T. Clark; Zhanbing Ren (Frontiers Media S.A., 2022)
AimEvidence demonstrates the negative impact of excessive screen-based sedentary time (screen-based sedentary behavior; SSB) on mental health in adolescents. However, little is known regarding the associations between different types of SSBs and anxiety symptoms in adolescents. Thus, this study sought to explore the associations between different types of SSBs and anxiety symptoms in a sample of Chinese adolescents.MethodsA web-based questionnaire survey was used to collect data. In total, 1,998 study participants conveniently recruited in Guangdong Province completed the questionnaire. Of them, 1,331 study participants provided valid data for variables of interest. SSB was categorized into television/movie time, video game time, and internet-surfing time. Anxiety symptoms were assessed using Zung Self-Rating Anxiety Scale, a validated assessment in Chinese youth populations. Generalized linear models were used to explore the associations between different types of SSBs and anxiety symptoms.ResultsIn adolescents, video game time of 6 or more h was positively and significantly associated with anxiety symptoms (odds ratio = 5.25, 95% CI: 1.86-14.84, p < 0.01). This association was also observed specifically in boys (odds ratio = 5.12, 95% CI: 1.56-17.44, p < 0.05); however, in girls, there were no associations between different types of SSBs and anxiety symptoms.ConclusionInterventions aiming at reducing video games in adolescents, especially in boys, should be designed to prevent anxiety symptoms. This kind of intervention should also take sex differences into consideration. Future studies are encouraged to confirm the veracity of the findings in this study.